Pengaruh Digital Marketing dan Viral Marketing terhadap Keputusan Pembelian Facial Wash Kahf di Tokopedia (Studi Kasus pada Mahasiswa Prodi Teknik Mesin Politeknik Negeri Medan) - Panjaitan, Supri; Nasution, Amrin Mulia Utama; Sabrina, Hesti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This research aims to determine the Influence of Digital Marketing and Viral Marketing on the Purchase Decision of Kahf Facial Wash on Tokopedia (Case Study on Students of the Mechanical Engineering Program at the Medan State Polytechnic). The type of research used in this study is a quantitative approach. The sampling technique used is purposive sampling. The sample in this study consists of mechanical engineering students at the Medan State Polytechnic and students who have purchased Kahf facial wash at least once on the Tokopedia platform, totaling 86 respondents. The data obtained using primary data in the form of questionnaires were analyzed using the multiple linear regression analysis method with the SPSS 26 program. Based on the hypothesis testing that 1) Digital Marketing (X1) has a positive and significant effect on purchasing decisions with a calculated t-value of 4.046, it is known that the calculated t-value is greater than the t-table value (1.988). And the p-value in the sig column is 0.010 < 0.05, which means it has a significant effect. 2) Viral marketing (X2) has a positive and significant effect on purchasing decisions. This can be seen from the significance value of 0.023 < 0.05 and the calculated t-value of 7.054 > t-table value (1.988). 3) Digital Marketing (X1) and Viral Marketing (X2) simultaneously have a positive and significant effect on purchasing decisions. This can be seen from the calculated F-value being greater than the F-table value and the significance level (0.000) being less than 0.05.